Waste to wealth: a Case study of papaya peel - Pathak, Pranav D. (Waste and Biomass Valorization, 2019)
Papaya is a popular fruit consumed worldwide and well-known for its food and nutritional values. It is used in food industries for the production of jams, jellies, etc. As a result, these industries generate huge amounts of papaya peel (PP) and seeds as by-products, which are typically considered a waste, and thus discarded. However, our current investigation indicates that PP is a valuable source of bioactive compounds, which can be converted into many value-added products. In this article, we review the physicochemical composition and valorization of PP. PP can be utilized to obtain many value-added products by fermentation (e.g., biofuels, adsorbents, dietary fibers, biomedicine, biomaterials). The biorefinery approach for PP will definitely increase the value of this waste by producing an array of value-added products and achieving zero waste generation.
Keywords: Bioactive compounds; Biorefinery; Papaya peel; Valorization; Value-added products